Double quantum well resonant tunneling negative differential resistance device design using graphene nanoribbons - Saha, Gobinda; Saha, Atanukumar; Harun-Ur Rashid, A.B.M. (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 15th IEEE International Conference on Nanotechnology, IEEE-NANO 2015; Rome; Italy; 27 July 2015 through 30 July 2015 [© 2015 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/NANO.2015.7388632